Contrast-Enhanced EUS for Differential Diagnosis of Pancreatic Masses: A Meta-Analysis - Sibin Mei; Mengyu Wang; Leimin Sun (Gastroenterology Research and Practice)
Background. Though methods for the diagnosis of pancreatic masses are various, such as ultrasonography (US), computed tomography (CT), endoscopic ultrasonography (EUS), and contrast-enhanced computed tomography (CE-CT), their sensitivity, specificity, and accuracy are not quite satisfying. Contrast-enhanced endoscopic ultrasonography (CE-EUS), as a new technique, has its own unique advantages in diagnosing pancreatic disease. However, its sensitivity, specificity, and accuracy are still controversial. Objective. To evaluate the accuracy of CE-EUS for differential diagnosis between benign and malignant pancreatic mass lesions. Design. Eighteen relevant articles systemically searched from PubMed, Web of Science, Ovid, Scopus, and MEDLINE were selected. The pooled results were calculated in a fixed effects model. Main Outcome Measurement. The pooled sensitivity, specificity, positive likelihood ratio (LR), negative likelihood ratio, diagnostic odds ratio (OR), and summary receiver operating characteristic (SROC) curve. Results. The pooled sensitivity, specificity, and diagnostic odds ratio of CE-EUS for the differential diagnosis of pancreatic adenocarcinomas were 0.91 (95% confidence interval (CI), 0.89-0.93), 0.86 (95% CI, 0.83-0.89), and 69.50 (95% CI, 48.89-98.80), respectively. The SROC area under the curve was 0.9545. The subgroup analysis based on excluding the outliers showed that the heterogeneity was eliminated and the pooled sensitivity and specificity were 0.92 (95% CI, 0.90-0.93) and 0.87 (95% CI, 0.84-0.89), respectively. The SROC area under the curve was 0.9569. Conclusion. CE-EUS is a useful method to distinguish pancreatic adenocarcinoma from other pancreatic diseases. Compared with EUS elastography, it has higher specificity. However, it is still not superior to pathological diagnosis for the identification of pancreatic carcinomas.